2020
DOI: 10.3390/s20020365
|View full text |Cite
|
Sign up to set email alerts
|

Sensor Technologies to Manage the Physiological Traits of Chronic Pain: A Review

Abstract: Non-oncologic chronic pain is a common high-morbidity impairment worldwide and acknowledged as a condition with significant incidence on quality of life. Pain intensity is largely perceived as a subjective experience, what makes challenging its objective measurement. However, the physiological traces of pain make possible its correlation with vital signs, such as heart rate variability, skin conductance, electromyogram, etc., or health performance metrics derived from daily activity monitoring or facial expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 322 publications
0
28
0
Order By: Relevance
“…Many of the limitations observed in these studies can be overcome by increasing patient sizes in RCTs, standardization of the intervention protocols, and moving from subjective to objective pain and immersion measurements. For example, studies have shown that biophysical parameter measurements, such as heart rate variability (HRV) and skin conductance using sensor-based pain monitoring technologies, can help measure pain objectively (Naranjo-Hernández et al, 2020). Though research on the immersion process is still in its infancy, the degree of immersion has been found to be a critical factor in improving the target patient engagement (Servotte et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Many of the limitations observed in these studies can be overcome by increasing patient sizes in RCTs, standardization of the intervention protocols, and moving from subjective to objective pain and immersion measurements. For example, studies have shown that biophysical parameter measurements, such as heart rate variability (HRV) and skin conductance using sensor-based pain monitoring technologies, can help measure pain objectively (Naranjo-Hernández et al, 2020). Though research on the immersion process is still in its infancy, the degree of immersion has been found to be a critical factor in improving the target patient engagement (Servotte et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Most of them have only focused on pain recognition, which means that they just indicated statistical significance correlations between individual physiological signals and pain to recognize the presence or absence of pain, without quantifying the pain intensity. Naranjo-Hernández et al [ 21 ] provided a detailed review of different sensors that have been proposed for objective evaluation of chronic pain.…”
Section: Related Workmentioning
confidence: 99%
“…Finally, some works have carried out reviews of sensor technologies compatible with BSN. In this sense, the authors of Reference [ 8 ] carry out a detailed review of the different technologies that have been proposed for the objective evaluation of chronic pain, which is prevalent in multiple pathologies. The chronic pain condition is directly related to the patient’s well-being, and also to the psychological state (anxiety, depression, etc.).…”
Section: Review Articles In the Context Of Bsnmentioning
confidence: 99%
“…Objective pain assessment is challenging for researchers, and different approaches for pain measurement based on biomedical sensors have been proposed, although to date there is no universal method for the objective pain assessment. The referenced work [ 8 ] reviews and comparatively analyzes the different methods described in the literature focusing on chronic non-cancer pain. One of the variables employed in the studies is the heart rate variability (HRV), since pain influences the balance of the autonomic nervous system (ANS), detectable through the analysis of HRV.…”
Section: Review Articles In the Context Of Bsnmentioning
confidence: 99%